PENGARUH PERTUMBUHAN PERUSAHAAN, KONDISI KEUANGAN PERUSAHAAN, DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP OPINI AUDIT GOING CONCERN - Danang Anugrah Putra; Ach. Syaiful Hidayat Anwar; Thoufan Nur (Universitas Muhammadiyah Malang, 2017)
This research is aimed to examine the effect of the company’s growth, financial condition and theprior year audit opinion on going concern audit opinion in mining companies listed on IndonesiaStock Exchange (IDX). This research is associativeresearch that the population of this researchis mining companies listed on Indonesia Stock Exchange (IDX) during period 2011-2015. Thesample is determined by purposive sampling method and the technique of data analysis islogistic regression. The results of this research are company’s growth and the prior year auditopinion has no effect on going concern audit opinion. On the other hand, financial condition haseffect on going concern audit opinion.Keywords:Audit Opinion, Financial Condition, Going Concern, The Company’s Growth